Dbx2, an Aging-Related Homeobox Gene, Inhibits the Proliferation of Adult Neural Progenitors - Andrea Giuliani; Valerio Licursi; Paola S. Nisi; Mario Fiore; Sara D’Angelo; Stefano Biagioni; Rodolfo Negri; Peter J. Rugg-Gunn; Emanuele Cacci; Giuseppe Lupo (Stem Cell Reviews and Reports, 2023)
In the adult mouse brain, the subventricular zone (SVZ) underlying the lateral ventricles harbours a population of quiescent neural stem cells, which can be activated (aNSCs) to initiate proliferation and generate a neurogenic lineage consisting of transit amplifying progenitors (TAPs), neuroblasts (NBs) and newborn neurons. This process is markedly reduced during aging. Recent studies suggest that the aged SVZ niche decreases the pool of proliferating neural/stem progenitor cells (NSPCs), and hence adult neurogenesis, by causing transcriptomic changes that promote NSC quiescence. The transcription factors that mediate these changes, however, remain unclear. We previously found that the homeobox gene Dbx2 is upregulated in NSPCs of the aged mouse SVZ and can inhibit the growth of NSPC cultures. Here, we further investigate its role as a candidate transcriptional regulator of neurogenic decline. We show that Dbx2 expression is downregulated by Epidermal Growth Factor receptor signaling, which promotes NSPC proliferation and decreases in the aged SVZ. By means of transgenic NSPC lines overexpressing Dbx2 , we also show that this gene inhibits NSPC proliferation by hindering the G2/M transition. Furthermore, we exploit RNA sequencing of transgenic NSPCs to elucidate the transcriptomic networks modulated by Dbx2 . Among the top hits, we report the downregulation of the molecular pathways implicated in cell cycle progression. Accordingly, we find that Dbx2 function is negatively correlated with the transcriptional signatures of proliferative NSPCs (aNSCs, TAPs and early NBs). These results point to Dbx2 as a transcription factor relaying the anti-neurogenic input of the aged niche to the NSPC transcriptome. Graphical Abstract

Active microbial ecosystem in Iron‐Age tombs of the Etruscan civilization - Angela Cirigliano; Francesco Mura; Adele Cecchini; Maria Cristina Tomassetti; Daniele Federico Maras; Monica Di Paola; Niccolò Meriggi; Duccio Cavalieri; Rodolfo Negri; Andrea Quagliariello; John E. Hallsworth; Teresa Rinaldi (Environmental Microbiology, 2021)
Summary Earth's microbial biosphere extends down through the crust and much of the subsurface, including those microbial ecosystems located within cave systems. Here, we elucidate the microbial ecosystems within anthropogenic 'caves'; the Iron‐Age, subterranean tombs of central Italy. The interior walls of the rock (calcium‐rich macco ) were painted ~2500 years ago and are covered with CaCO 3 needles (known as moonmilk). The aims of the current study were to: identify biological/geochemical/biophysical determinants of and characterize bacterial communities involved in CaCO 3 precipitation; challenge the maxim that biogenic activity necessarily degrades surfaces; locate the bacterial cells that are the source of the CaCO 3 precipitate; and gain insight into the kinetics of moonmilk formation. We reveal that this environment hosts communities that consist primarily of bacteria that are mesophilic for temperature and xerotolerance (including Actinobacteria, Bacteroidetes and Proteobacteria); is populated by photosynthetic Cyanobacteria exhibiting heterotrophic nutrition ( Calothrix and Chroococcidiopsis ); and has CaCO 3 precipitating on the rock surfaces (confirmation that this process is biogenic) that acts to preserve rather than damage the painted surface. We also identified that some community members are psychrotolerant ( Polaromonas ), acidotolerant or acidophilic (members of the Acidobacteria ), or resistant to ionizing radiation ( Brevundimonas and Truepera ); elucidate the ways in which microbiology impacts mineralogy and vice versa ; and reveal that biogenic formation of moonmilk can occur rapidly, that is, over a period of 10 to 56 years. We discuss the paradox that these ecosystems, that are for the most part in the dark and lack primary production, are apparently highly active, biodiverse and biomass‐rich.

General features of the transcriptional response of mammalian cells to low- and high-LET irradiation - Nicoletta Giusti; Francesca Bufalieri; Valerio Licursi; Tiziana Castrignanò; Mattia D’Antonio; Roberto Amendola; Rodolfo Negri (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

A proposed integrated systems approach to the radiation biology of cosmic interest: biophysics and molecular characterization of tissues irradiated with 14 MeV neutrons - Valerio Licursi; Emiliano Fratini; Barbara Benassi; Mariangela Cestelli-Guidi; Claudia Consales; Augusto Marcelli; Chiara Mirri; Rodolfo Negri; Roberto Amendola (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)

Summer autotrophy and winter heterotrophy in the temperate symbiotic coral Cladocora caespitosa - C. Ferrier-Pagès; A. Peirano; M. Abbate; S. Cocito; A. Negri; C. Rottier; P. Riera; R. Rodolfo-Metalpa; S. Reynaud (Limnology and Oceanography, 2011)
Carbon and nitrogen isotope ratios ( δ 13 C and δ 15 N) were determined in the zooxanthellae, host tissue, and whole symbiotic association of the symbiotic temperate coral Cladocora caespitosa , as well as in the different components of the coral's potential food sources (plankton, particulate organic matter in seawater and in the sediment). Data were collected both in winter and summer at three different locations, to assess the extent of auto‐ and heterotrophy in this species and get a better understanding of the functioning of temperate symbioses. There was a marked seasonal difference in the signature of the zooxanthellae and host tissue, highlighting two clear feeding patterns. In summer, δ 13 C signatures of the coral host and the zooxanthellae were similar (‐17‰) and very different from the signature of the food sources (from ‐21‰ to ‐25‰), suggesting that corals were relying on autotrophy for the acquisition of carbon. δ 15 N values also suggested that nitrogen was not acquired through feeding. Conversely, in winter, the δ 13 C signature of the host decreased by ca. ‐23‰ to ‐28‰, and was more comparable to the signature of the external food sources (between ‐24‰ and ‐25‰), suggesting a substantial reliance of C. caespitosa on external food sources during this season. There was also a 3‰ enrichment between the δ 15 N signatures of the food (4‐5‰) and the signature of the symbiotic association (7‐8‰), suggesting that nitrogen was also acquired through feeding. Overall, these results give evidence that C. caespitosa and temperate corals in general derive a large fraction of their energy from heterotrophic feeding in winter.

Selenite transiently represses transcription of photosynthesis-related genes in potato leaves - Valeria Poggi; Valerio Del Vescovo; Claudio Di Sanza; Rodolfo Negri; Alejandro Hochkoeppler (Photosynthesis Research, 2008)